Corrigendum to "Plasmon aided (BiVO4)x–(TiO2)1−x ternary nanocomposites for efficient solar water splitting" [Solar Energy 155 (2017) 770–780]. (October 2018) - Ali, Shahid; Khan, Ibrahim; Khan, Safyan A.; Sohail, Manzar; Yamani, Zain H.; Morsy, Mohamed A.; Qamaruddin, Muhammad
Graphical abstract: